RANCANG BANGUN ALAT PENGERING BUAH PINANG MENGGUNAKAN METODE PEMBAKARAN BIOMASSA: Design and Construction of Nut Dryer Using Biomass Combustion Method - Muhammad Ivanto; Muhammad Taufik; Titien Pertiwi; Agil Hendrawan (Universitas Darussalam Gontor, 2022)
The areca drying using the biomass burning method is one of the drying methods offered in the areca nut drying process in addition to using solar energy. So far, it is considered less effective in the drying process due to the lack of time needed up to 14 days and also very dependent on weather conditions that often change. The process of drying areca nut is very under environmental conditions where the ideal temperature in the process of drying areca nut ranges from 35oC-45oC in hot sun conditions, while using a dryer the optimal temperature is between 65oC-70oC. The betel nuts used is ripe betel nut with water content indicators above 65% while the percentage of dried betel nut is below 11% water content contained in the betel nut. The biomass burning method in this study was using firewood, husks and empty bunches. The working principle of this tool is by utilizing combustion from a pipe in the combustion chamber where the pipe temperature will rise, then air will enter through the thrust contained on the outside of the pipe, then the air temperature will rise downwards. ambient temperature then the air will enter the drying system or oven so that the drying process runs. The purpose of this research is to speed up the drying process of areca nut where the drying method takes about 14 days, while the drying time using a areca dryer explores 5-10 days so that it can save drying time. The results obtained from this drying process where the biomass burning method is divided into 3 fuels, namely firewood, husks and empty fruit bunches, the results of the drying time using biomass are 6 days with each temperature of 65°C-70°C, 55°C-60°C & 45°C-50°C and the average yield ratio of areca nut drying was 10%, 27.1%, and 29.6%. The duration and the maximum temperature achieved are strongly influenced by the quality of the fuel, the greater the residue of the fuel, the lower the maximum temperature of combustion.